Membrane-bound and exosomal metastasis-associated C4.4A promotes migration by associating with the α6β4 integrin and MT1-MMP1,2 - Ngora, Honoré; Galli, Uwe; Miyazaki, Kaoru; Zöller, Margot (Neoplasia, 2012)
Metastasis-associated C4.4A, which becomes upregulated during wound healing and, in some tumors, during tumor progression, is known to be frequently associated with hypoxia. With the function of C4.4A still unknown, we explored the impact of hypoxia on C4.4A expression and functional activity. Metastatic rat and human tumor lines upregulate C4.4A expression when cultured in the presence of CoCl2. Although hypoxia-inducible factor 1α (HIF-1α) becomes upregulated concomitantly, HIF-1α did not induce C4.4A transcription. Instead, hypoxia-induced C4.4A up-regulation promoted in vivo and in vitro wound healing, where increased migration on the C4.4A ligands laminin-111 and -332 was observed after a transient period of pronounced binding. Increased migration was accompanied by C4.4A associating with α6β4, MT1-MMP1, and TACE and by laminin fragmentation. Hypoxia also promoted the release of C4.4A in exosomes and TACE-mediated C4.4A shedding. The association of C4.4A with α6β4 and MT1-MMP1 was maintained in exosomes and exosomal α6β4- and MT1-MMP1-associated C4.4A but not shed C4.4A sufficient for laminin degradation. Hypoxia-induced recruitment of α6β4 toward raft-located C4.4A, MT1-MMP, and TACE allows for a shift from adhesion to motility, which is supported by laminin degradation. These findings provide the first explanation for the C4.4A contribution to wound healing and metastasis.